Persistent Pain Maintains Morphine-Seeking Behavior after Morphine Withdrawal through Reduced MeCP2 Repression of Glua1 in Rat Central Amygdala - Hou, Yuan-Yuan (J Neurosci, 2015)
As long-term opioids are increasingly used for control of chronic pain, how pain affects the rewarding effect of opioids and hence risk of prescription opioid misuse and abuse remains a healthcare concern and a challenging issue in current pain management. In this study, using a rat model of morphine self-administration, we investigated the molecular mechanisms underlying the impact of pain on operant behavior of morphine intake and morphine seeking before and after morphine withdrawal. We found that rats with persistent pain consumed a similar amount of daily morphine to that in control rats without pain, but maintained their level-pressing behavior of morphine seeking after abstinence of morphine at 0.2 mg/kg, whereas this behavior was gradually diminished in control rats. In the central nucleus of amygdala (CeA), a limbic structure critically involved in the affective dimension of pain, proteins of GluA1 subunits of glutamate AMPA receptors were upregulated during morphine withdrawal, and viral knockdown of CeA GluA1 eliminated the morphine-seeking behavior in withdrawn rats of the pain group. Chromatin immunoprecipitation analysis revealed that the methyl CpG-binding protein 2 (MeCP2) was enriched in the promoter region of Gria1 encoding GluA1 and this enrichment was significantly attenuated in withdrawn rats of the pain group. Furthermore, viral overexpression of CeA MeCP2 repressed the GluA1 level and eliminated the maintenance of morphine-seeking behavior after morphine withdrawal. These results suggest direct MeCp2 repression of GluA1 function as a likely mechanism for morphine-seeking behavior maintained by long-lasting affective pain after morphine withdrawal.